2016
DOI: 10.1371/journal.pone.0156993
|View full text |Cite
|
Sign up to set email alerts
|

Transcript Profile of Flowering Regulatory Genes in VcFT-Overexpressing Blueberry Plants

Abstract: In order to identify genetic components in flowering pathways of highbush blueberry (Vaccinium corymbosum L.), a transcriptome reference composed of 254,396 transcripts and 179,853 gene contigs was developed by assembly of 72.7 million reads using Trinity. Using this transcriptome reference and a query of flowering pathway genes of herbaceous plants, we identified potential flowering pathway genes/transcripts of blueberry. Transcriptome analysis of flowering pathway genes was then conducted on leaf tissue samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(79 citation statements)
references
References 32 publications
4
74
0
Order By: Relevance
“…Our quantitative RT–PCR results confirmed the upregulation (six genes) and downregulation (four genes) of all selected genes (Supplementary Figure S5). In addition to our previous confirmation of the selected DE flowering pathway genes, 39 our quantitative RT–PCR results gave more evidence to support the reliability of our RNA sequencing data.…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Our quantitative RT–PCR results confirmed the upregulation (six genes) and downregulation (four genes) of all selected genes (Supplementary Figure S5). In addition to our previous confirmation of the selected DE flowering pathway genes, 39 our quantitative RT–PCR results gave more evidence to support the reliability of our RNA sequencing data.…”
Section: Resultssupporting
confidence: 79%
“…Because VcSOC1 can interact with GA pathway genes and the ‘VcFT-Aurora’ plants showed retarded growth, we hypothesized that the VcFT -OX has a potential impact on retarded plant growth through the expression of either phytohormone genes or dwarf-related genes. Using the annotated RNA sequencing data of our previous samples, 39 in-depth analysis in this study revealed the overall effect of the VcFT -OX on blueberry gene networks (Figure 4). …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations